2012
DOI: 10.1177/0884533611433534
|View full text |Cite|
|
Sign up to set email alerts
|

Zinc and Liver Disease

Abstract: Zinc is an essential trace element required for normal cell growth, development, and differentiation. It is involved in DNA synthesis, RNA transcription, and cell division and activation. It is a critical component in many zinc protein/ enzymes, including critical zinc transcription factors. Zinc deficiency/altered metabolism is observed in many types of liver disease, including alcoholic liver disease (ALD) and viral liver disease. Some of the mechanisms for zinc deficiency/ altered metabolism include decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
135
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(145 citation statements)
references
References 128 publications
3
135
0
2
Order By: Relevance
“…Zinc supplementation to patients with ALD reversed impaired night vision, skin lesions, and immune dysfunction (25). Both animal and cell culture studies showed that zinc deprivation increased fat accumulation, inflammatory cell infiltration, and apoptotic hepatocytes (15,38,39).…”
mentioning
confidence: 99%
“…Zinc supplementation to patients with ALD reversed impaired night vision, skin lesions, and immune dysfunction (25). Both animal and cell culture studies showed that zinc deprivation increased fat accumulation, inflammatory cell infiltration, and apoptotic hepatocytes (15,38,39).…”
mentioning
confidence: 99%
“…Antioxidant function, promotion of the antiviral effect of interferon, an inhibitory effect on HCV replication, and regulation of imbalances between T helper 1 (TH1) and T helper 2 (TH2) have been considered as probable mechanisms for the effectiveness of zinc in treatment of HCV infection [16,17]. In recent clinical studies, the addition of zinc to the standard treatment regimen for chronic hepatitis C produced limited benefits [8]. For example, Murakami et al, evaluated the addition of polaprezinc 150 mg/d to the combination of Peg INF-α and ribavirin in 21 patients with hepatitis C in a randomized study.…”
Section: Resultsmentioning
confidence: 99%
“…For the first time zinc deficiency due to interferon has been reported by Gainer [7]. In previous studies, the addition of zinc to the standard therapy for hepatitis C induced limited benefits to viral response and some of these studies have reported improved transaminases with zinc therapy [8]. It is important to note that a group of patients with hepatitis C have beta thalassemia major as well and combination therapy with Peg INF-α and ribavirin should be suggested for them…”
Section: Introductionmentioning
confidence: 99%
“…Absorption of Zn is concentration dependent and occurs throughout the small intestine (mainly jejunum). Absorption may be impaired in cirrhosis, and typically there is increase urinary excretion of Zn in cirrhosis [7].…”
Section: Introductionmentioning
confidence: 99%